Pertanggungjawaban Pidana Terhadap Jabatan Dalam Tindak Pidana Korupsi Pengadaan Barang Dan Jasa - Miru, Grazia Vione; Nirahua, Salmon Eliazer Marthen; Wadjo, Hadiba Zachra (PATTIMURA Legal Journal, 2023)
Introduction: The element of “abusing authority” is a core part of the corruption offense. Purposes of the Research: Abuse of authority is a form of unlawful act. Methods of the Research: The method in this study was carried out using the type of research used was normative legal research. The approach to the problem used in this paper is a statutory approach. The sources of legal materials use Primary Legal Materials and Secondary Legal Materials. The technique of collecting legal materials uses statutory regulations, books and the internet, which is also the technique of managing and analyzing legal materials using qualitative analysis methods. Results of the Research: In terms of carrying out the duties and authorities as a definitive official as well as a task-carrying official in the Southwest Maluku district communication and information office, the actions of an official based on the authority attached to his or her position are not necessarily free from legal problems. In order to continue the Runway construction work (Moa airport construction work) sourced from the 2012 Fiscal Year Budget, the defendant PM as a Budget User (PA) and as a Commitment Making Officer (PPK) because his negligence resulted in state financial losses